In-building telecommunications infrastructure - Gonzalo Zuloaga; Thomas Plückebaum (WIK Wissenschaftliches Institut für Infrastruktur und Kommunikationsdienste, 2022)
The newly passed German telecommunication regulation has set the deployment and sharing conditions of in-building infrastructure with the purpose of addressing the need of generating proper incentives to network operators to invest in and extend their very high capacity access networks. At the same time, this should help reducing the gap of gigabit speeds reaching end user's buildings door step but not their actual homes. This paper analyses relevant technical aspects of deploying and sharing in-building infrastructures. Particularly, we address, from a technical perspective, the requirements that different transmission technologies have on different in-building infrastructures, the opportunities and limitations on sharing in-building infrastructure, as well as the shortcomings of certain types of in-building infrastructure and topologies in achieving the gigabit objectives. We provide an overview and technical comparison of the different in-building network installations and technologies that are predominantly available in Germany in order to assess which are capable to ensure a delivery of 1 Gbps (in down- and upstream communication) to the end user. In this context, we analyse the implications that the identified technologies have on promoting open access to the building and therefore competition among network providers. By going beyond the new regulation, this paper also assesses the role of standardisation of in-building infrastructure, in securing investments in very high capacity access networks and keeping the infrastructure adaptable to new developments in the future. In absence of binding standards, we gather a set of practical recommendations promoted by German institutions regarding the deployment of new in-building infrastructure. – – Das neue Telekommunikationsgesetzt regelt Ausbau und Mitnutzungsmöglichkeiten für gebäudeinterne Telekommunikationsinfrastrukturen mit dem Ziel, Netzbetreiber zu bewegen, auch in diese Infrastrukturen zu investieren um Endkunden mit 1 Gbit/s Breitbanddiensten versorgen zu können. Dies soll die Lücke schließen zwischen der Versorgung in der Straße und dem Anschluss in der Wohnung. Wir beschränken uns in dieser Studie auf die relevanten technischen Aspekte zum Ausbau und Mitnutzen gebäudeinterner Infrastrukturen. Insbesondere untersuchen wir die Anforderungen der unterschiedlichen Übertragungstechnologien an die gebäudeinternen Infrastrukturen, die Optionen und Grenzen der Mitnutzung und die Begrenzungen einzelner Infrastrukturen in Hinsicht auf deren Nutzung für eine Gibgabit Übertragung. Ein Überblick und technischer Vergleich bestehender, in Deutschland marktüblicher Infrastrukturen erlaubt zu bewerten, welche von Ihnen sich für eine symmetrische Gigabit Übertragung eignen und wie gut sie geeignet sind, einen Infrastrukturwettbewerb zu unterstützen. Die Studie geht darüber hinaus auf die Rolle der Standardisierung gebäudeinterner Infrastrukturen ein, ihre Flexibilität für zukünftige Veränderungen und ihre Eignung zur Wahrung der Investitionssicherheit. Zudem stellt sie die Frage nach konkreten geeigneten Standards und deren Verbindlichkeit und bewertet Vorschläge deutscher Organisationen dazu.
Keywords: 330